Postage stamp commemorating the Natural Rubber Conference in Kuala Lumpur, Malaysia, 1968 (1968)
Stamp was issued on the occasion of a Natural Rubber Conference held in Kuala Lumpur, Malaysia, in 1968. It depicts a space-filling model of isoprene and a representation of the traditional way of collecting natural rubber latex from a tapped tree.
Keywords: Postage stamps; Malaysia; Latex; Rubber industry and trade; Isoprene; Science on postage stamps; Rubber plants; Commemorative postage stamps